The effect of various concentrations of probiotics in commercial feed on the growth of koi fish (Cyprinus rubrofuscus) - Buana, Bima Galang Buana; Lesmana, Dudi; Mulyana; Farastuti, Eko Rini (Universitas Djuanda, 2025)
Cyprinus rubrofuscus has high economic value as a freshwater ornamental fish, in demand in the international market. The growth of koi fish can be increased by adding probiotics to the feed. This addition can benefit fish health and water quality if given in the correct dose. This study was conducted to see the effect of different doses of probiotics in the feed on koi growth. The study was conducted from February 2023 to February 2024, with treatments administered from May 28 to July 7, 2023. The design was a Completely Randomized Design (CRD) of four treatments (PB0, PB10, PB15, PB20) with three replications. The parameters measured included growth in length, weight, specific growth rate, and survival. At the end of the study, it was found that adding probiotic doses had a significant effect (P < 0.05) on weight, length, and specific growth rate, but did not affect survival. The PB15 dose gave the best results, with a weight gain of 0.46 ± 0.66 g and a particular growth rate of 1.88 ± 0.11% per day.